BIBLIOMETRIC STUDY OF FINANCIAL LITERACY AND RISK TOLERANCE ON INVESTMENT DECISIONS - Nisa, Karimatun; Wahono, Puji; Silaningsih, Endang (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to analyze trends and developments in research on the relationship between financial literacy, risk tolerance, and investment decisions. Employing a bibliometric analysis methodology, the study utilizes data from international publications in the Google Scholar database collected through Publish or Perish software. The analysis covers the publication period from 2017 to 2022 and includes a review of 498 articles using keywords such as financial literacy, risk tolerance, and investment decisions. VOSviewer software was employed for data analysis. The analysis reveals increased attention to topics such as risk appetite, financial markets, and performance, despite a declining trend in publications on financial literacy, risk tolerance, and investment decisions. Significant gaps in the literature are identified, particularly in areas such as financial risk tolerance, financial education, enterprise risk management, and investment horizon. Â Future research should focus on these underexplored areas to develop personalized investment strategies and enhance financial education. Recommendations include the creation of targeted financial education programs and tools to improve the assessment of risk tolerance. This study provides valuable insights into the evolving landscape of financial literacy and risk tolerance research. It underscores the importance of these factors in making informed investment decisions and offers a foundation for future studies to build upon.